Incubating Leaders in Maine - McDonnell, Joseph (Maine Policy Review, 2018)
For a sparsely populated state, Maine has produced an extraordinary number of national, bipartisan leaders. What has made Maine an incubator for such leadership? Alexis de Tocqueville, the author of Democracy in America, provides useful insights into Maine’s culture as a breeding ground for its leadership. But rapid societal changes sweeping the country and the world—particularly globalization, urbanization, and the digitization of the economy—will inevitably alter Maine’s culture. This paper explores steps Maine might take to develop leaders in this new environment by preserving its past strengths and adjusting to these new challenges. Maine could overcome its north/south divide and play a role in developing leaders who would bring polarized sectors of the country together.